Hairy Cell Leukemia Masquerading as Pancytopenia in Pregnancy. (21st August 2019) - Shackleton, Louisa; Langabeer, Stephen E.; O'Brien, David; McCarron, Sarah L.; Byrne, Bridgette; Barry, Rupert; Flavin, Richard; Bacon, C. Larry; Flynn, Catherine M.
Abstract : Thrombocytopenia is one of the most common hematological abnormalities observed during pregnancy, and in rare cases, this may be the first indicator of an underlying hematological malignancy. Hairy cell leukemia (HCL) is an uncommon B-cell lymphoproliferative disorder of which thrombocytopenia is a recurrent presenting feature. A case of pancytopenia presenting in pregnancy is described in which the thrombocytopenia persisted postpartum coincidental with a vesicular, pustular rash characterised as Sweet's syndrome. Hematological, histological, immunophenotypic, and molecular investigations confirmed the presence of HCL. The patient was treated with cladribine resulting in resolution of Sweet's syndrome, hematological remission from HCL, and achievement of a normal platelet count. This case highlights the need to maintain a wide differential diagnosis for presentations of pancytopenia or thrombocytopenia in pregnancy and the requirement for follow-up investigation of unusual cases with a lack of response to steroids or immunoglobulin.